Phase Ib/II single-arm trial evaluating the combination of everolimus, lapatinib and capecitabine for the treatment of HER2-positive breast cancer with brain metastases (TRIO-US B-09). (November 2018) - Hurvitz, Sara; Singh, Rashi; Adams, Brad; Taguchi, Julie A.; Chan, David; Dichmann, Robert A.; Castrellon, Aurelio; Hu, Eddie; Berkowitz, Jonathan; Mani, Aruna; DiCarlo, Brian; Callahan, Rena; et al.
Background: Improving outcomes for patients with human epidermal growth factor 2-positive (HER2+) central nervous system (CNS) metastases remains an unmet clinical need. This trial evaluated a novel combination of everolimus, lapatinib and capecitabine for this disease. Methods: Patients with trastuzumab-pretreated, HER2+ breast cancer brain metastasis without prior therapy with a mammalian target of rapamycin (mTOR) inhibitor were eligible. Patients received lapatinib and everolimus daily (continuously) and capecitabine twice daily (d1–14) in 21-d cycles. The primary endpoint was the 12-week CNS objective response rate (ORR). Secondary endpoints included safety, progression-free survival (PFS), overall survival (OS), best CNS ORR and extra-CNS ORR. Results: A total of 19 participants were enrolled and treated with ⩾1 dose of the study drug. The median age was 58.5 years, the median number of therapies for metastatic breast cancer was 2.5 (0–11). Pretrial, 74% of participants had received prior lapatinib, capecitabine or both. A total of 63% had received previous CNS radiation or surgical resection and CNS radiation. The maximum tolerated doses were lapatinib at 1000 mg, everolimus at 10 mg, and capecitabine at 1000 mg/m 2 . Phase II proceeded with capecitabine at 750 mg/m 2 due to better tolerability. The most common grade 3/4 adverse events were mucositis (16%), diarrhea, fatigue, and hypokalemia (11% each). Of 11 participants evaluable for 12-week CNS ORR, 3 (27%) had partial response and 7 (64%) had stable disease. The best CNS ORR in eligible participants was 28% (5/18). The median PFS and OS were 6.2 and 24.2 months, respectively. Conclusions: This novel triplet combination of lapatinib, everolimus, and capecitabine is well tolerated and yielded a 27% response rate in the CNS at 12 weeks in heavily pretreated participants. Larger studies are warranted to further evaluate this regimen. Trial registration: ClinicalTrials.gov: NCT01783756. Registered 05 February 2013, https://clinicaltrials.gov/ct2/show/NCT01783756